Development Mathematics Realistic Education Worksheet Based on Ethnomathematics in Elementary School - Nurul Sari; Salafudin Salafudin; Muhammad Sugeng Sholehuddin; Alimatul Sholikhah (Phenomenon : Jurnal Pendidikan MIPA, 2022)
Learning mathematics at the elementary school level is an interesting to research. This is due to the mathematical material that requires children to reason mathematically. Many learning models are introduced to students, but are not in accordance with the surrounding cultural conditions. Culture is something that is close and real in students' lives. The purpose of this research is to see the effectiveness of ethnomathematics-based realistic mathematics learning in elementary school. Realistic mathematics learning model based on ethnomathematics in elementary schools can be implemented with the help of worksheets that contain guided reinvention and didactical phenomenology and self-developed models with ethnomathematical-based materials in the form of batik typical of Pekalongan. This research is a research and development research which includes a define, design, development, and dissemination. Data collection techniques were carried out using observation, interviews, questionnaires, tests, and documentation methods. The data analysis technique was carried out with the Independent t-test to determine the effectiveness of the learning model. The results of this study indicate that 1) LKS is feasible to use as a source of practical, valid, and effective mathematics learning tools, 2) ethnomathematics-based realistic mathematics learning is effective viewed from student learning outcomes in elementary school.